Response to afatinib in treatment-naïve patients with advanced mutant epidermal growth factor receptor lung adenocarcinoma with brain metastases. Issue 1 (2nd January 2018) - Li, Shih-Hong; Liu, Chien-Ying; Hsu, Ping-Chih; Fang, Yueh-Fu; Wang, Chun-Chieh; Kao, Kuo-Chin; Tseng, Li-Chuan; Yang, Cheng-Ta
ABSTRACT: Background : Brain metastases are observable in 20–40% of non-small cell lung cancer patients, but standard treatments for such metastases may be intolerable to some. Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) were found to be effective against mutant-EGFR lung adenocarcinomas, but data regarding their effectiveness, especially for the second-generation EGFR-TKI afatinib, is limited. This study compared key outcomes for afatanib monotherapy versus afatinib combined with whole-brain radiotherapy (WBRT) in treatment-naïve lung adenocarcinoma patients harboring EGFR mutations. Methods : A retrospective review of 28 brain metastatic lung adenocarcinoma patients treated between June 2014 and December 2016 was conducted; 17 were treated with WBRT and maintenance afatinib therapy, while 11 received afatinib monotherapy. Results : The patients were predominantly female (n = 17, 60.7%) and non-smokers (78.6%). Almost all the patients (89.3%) had an Eastern Cooperative Oncology Group performance status of 0–2. The EGFR mutation type consisted of the del19 mutation in 57.1% of the patients (n = 16), while L858R mutations were found in 42.9% (n = 12). The mean number of brain metastases (6.1 ± 5.0) was higher among the patients treated with afatinib monotherapy, while the mean size of the largest brain metastasis (19.0 ± 10.5mm) was greater in the afatinib combined with WBRT group. The objective response rates for the afatinib monotherapy and combination therapy groups were 81.8% and 88.2%, respectively. However, the monotherapy group exhibited a significantly higher complete response rate for intracranial lesions (63.6% vs. 17.6%, p  = 0.02), and there were no significant differences between the two treatment groups in overall survival or time to treatment failure. Conclusion : Afatinib can provide therapeutic efficacy and a good response rate in treatment-naïve mutant-EGFR lung adenocarcinoma patients with brain metastases regardless of whether or not they also receive radiotherapy.